1980
DOI: 10.1037/0021-843x.89.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting sex differences in the expression of depression.

Abstract: Large samples of college students indicated the degree to which they would engage in a number of behaviors or cognitions if depressed. The rated items were gathered using procedures suggested by the behavioral-analytic model. Factor analyses were employed to categorize items into interpretable variables.Stepwise discriminant function analyses were performed to determine maximum separation of male and female groups. Results augmented previous findings in this area. Men and women showed distinct differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
32
0
3

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 25 publications
8
32
0
3
Order By: Relevance
“…In the few studies that have examined sex differences in coping behaviors and depression, there is evidence for gender differences (e.g., Funabiki, Bologna, Pepping, & Fitzgerald, 1980;Ilfeld, 1980;Rippere, 1976). For instance, such studies have agreed that women are more likely than men to cope by confiding in a friend.…”
mentioning
confidence: 94%
“…In the few studies that have examined sex differences in coping behaviors and depression, there is evidence for gender differences (e.g., Funabiki, Bologna, Pepping, & Fitzgerald, 1980;Ilfeld, 1980;Rippere, 1976). For instance, such studies have agreed that women are more likely than men to cope by confiding in a friend.…”
mentioning
confidence: 94%
“…Seven [15,16,18,20,21,23,24] studies examined gender differences in severity of depression. Four of those [16,20,21,24] found no gender differences and 3 studies [15,18,23] found that women get higher total scores on depression rating scales than men. In table 1, the studies performed in clinical samples are summarized.…”
Section: Studies Performed In Broader Samples Of Depressive Patientsmentioning
confidence: 99%
“…Studies concerning gender differences in the clinical presentation of depression have provided divergent results. Ten [5][6][7][8][9][10][11][12][13][14] studies concerned gender differences in clinical samples of depressive patients, whereas 11 [15][16][17][18][19][20][21][22][23][24][25] studies dealt with non-clinical samples such as college students [15] or undergraduate students [16].…”
Section: Introductionmentioning
confidence: 99%
“…Par exemple, des analyses factorielles des réponses des hommes et des femmes au Beck Depression Inventory (Beck et al, 1961) indiquent que les hommes pleurent peu, sont agressifs et développent des problèmes somatiques (troubles du sommeil et tension). Les femmes pleurent et sont irritables (Funabiki et al, 1980;Nolen-Hoeksema, 1987). …”
Section: La Vie Adulteunclassified
“…Des données provenant de questionnaires montrent que les hommes parlent moins que les femmes des émotions négatives qu'ils ressentent (Aries et Johnson, 1983 ;Padesky et Hammen, 1981 ;Tschann, 1988). Contrairement à certaines femmes, ils ne manifestent pas de tendance à ruminer leurs émotions négatives et à les décrire dans un journal personnel (Funabiki et al, 1980). De plus, lorsqu'ils se sentent déprimés (selon les mesures du BDI), les hommes ne mentionnent jamais le mot «dépression» lorsqu'ils parlent aux autres de leurs problèmes (Fromkin et Warren, 1982, cit.…”
Section: La Vie Adulteunclassified